The economic consequences of financial fraud: evidence from the product market in China. Issue 1 (2nd January 2018) - Xin, Qingquan; Zhou, Jing; Hu, Fang
ABSTRACT: This article measures the spillover effect of the reputation loss induced by financial fraud on the product market. Using 294 regulatory penalties cases between 2004 and 2012, we find that, compared with the control firms, firms engaging in financial fraud exhibit a decline in sales revenue by 11.9–17.1% and a decrease in their gross profit margin on sales by 2.4–2.8% in the three years after punishment. Furthermore, we find that the sales revenue from the top five large customers falls 43.9–55.1% in the post-punishment period, while sales revenue from small customers does not decline significantly. Overall, our analyses suggest that the damaged reputation as a result of financial fraud has a major impact on the product market. Our findings help understand the trust mechanism in the Chinese product market.